Corporate innovation : case study E.ON - Dvořáčková, Anna (2019)
This thesis is about innovation management in company. It is about realising why innovation is important and that it needs to be given significant attention in a corporation. The analysis is based on literature review and interviews with involved companies. The findings show that management of innovation is pure in big companies. After the analysis there is set of recommendations that E.ON CZ should take into account.